PENGUKURAN NILAI INDEKS GLIKEMIK COOKIES TEPUNG TALAS BELITUNG (Xanthosoma sagittifolium) - Dian Fifit Sundari; Albiner Siagian; jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
One of the ways in treatment of nutritional problems is by eating through selection of setting the amount and type of carbohydrates that is appropriate to use the concept of the Glycemic Index (GI). GI is food levels according to their effect on blood glucose levels. Cocoyam (Xanthosoma sagittifolium) is a source of carbohydrate foods with a low glycemic index (GI = 50) and is often consumed by diabetics as a food substitute for rice. However, products of cocoyam such as cocoyam cookies have unknown glycemic index value. This study aimed to determined the glycemic index value of cocoyam cookies. This study was experimental study with 6 healthy subjects selected by purposive sampling method. Cocoyam used came from the district Hatonduhan. Measurement of glycemic index value performed by standard methods (Miller, 1996) with a food standard such as white bread. The portion of the test food and the standard food contained 50 g carbohydrate. The content of carbohydrates in cocoyam cookies was calculated by luff schroll method. GI was calculated by comparing the under kurve area of food test with food standard. Under kurve area of test food/ food standard was calculated by drawing horizontal and vertical lines thus forming wide awakes. Based on these calculations, the glycemic index value of cocoyam cocokies with white bread as a standard food is 79,9%. GI of cocoyam cookies included in high category (>70). It is recommended to further research to examine the glycemic index value of the other processed food that made from cocoyam (Xanthosoma sagittifolium). So it can add to list of foods that have an index glycemic value. Keywords : Glycemic index, cocoyam, cookies